2011
DOI: 10.1080/08927022.2011.592832
|View full text |Cite
|
Sign up to set email alerts
|

Computational structure characterisation tools in application to ordered and disordered porous materials

Abstract: In this article, we present a set of computational tools for systematic characterisation of ordered and disordered porous materials. These tools include calculation of the accessible surface area and geometric pore size distribution, analysis of the structure connectivity and percolation analysis of the porous space. We briefly discuss the algorithms behind these calculations. To demonstrate the capabilities of the tools and the type of insights that can be gained from their application, we consider a series o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
470
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 568 publications
(500 citation statements)
references
References 27 publications
27
470
0
3
Order By: Relevance
“…Effect of pore structure on the selectivity for CH 4 We noticed that the selectivity for methane in smaller pores (width < 1.2 nm) was remarkably higher, which is due to the reduction in entropy of hydrogen molecules and also due to the very high zero point energy of methane molecules in smaller pores.…”
Section: Introductionmentioning
confidence: 95%
“…Effect of pore structure on the selectivity for CH 4 We noticed that the selectivity for methane in smaller pores (width < 1.2 nm) was remarkably higher, which is due to the reduction in entropy of hydrogen molecules and also due to the very high zero point energy of methane molecules in smaller pores.…”
Section: Introductionmentioning
confidence: 95%
“…Geometric surface areas can be calculated by using a simple MC integration technique in which a nitrogen probe (3.681 Å ) molecule is rolled along the surface of the framework. [26,76,77] Walton and Snurr provided compelling evidence for the importance of calculating the BET surface area from the proper region of the adsorption isotherm. [75] Commercial 'BET' instruments are typically set to automatically choose a fixed range for BET fitting.…”
Section: Surface Area Void Fraction and Pore-size Distributionmentioning
confidence: 99%
“…The operator must ensure that the range results in consistent BET model parameters. The pore-size distribution (PSD) can be calculated geometrically in RASPA using the method of Gelb and Gubbins [77,78]. For every point in the void volume, the largest sphere is found that encloses the point but does not overlap with any framework atoms.…”
Section: Surface Area Void Fraction and Pore-size Distributionmentioning
confidence: 99%
“…This concept is essentially the same as the one proposed in a recent theoretical work, where linker removal was suggested as a potential method to increase the MOF pore volume and surface area. 29 Indeed, for a perfect UiO-66 crystal, the theoretical pore volume and surface area are modest: 0.426 cm 3 /g and 954 m 2 /g, respectively. For a crystal with 1 out of 12 linkers artificially removed for every metal center in the unit cell (i.e., a hypothetic model structure with ordered defects), the calculated values increase significantly to 0.502 cm Inspired by this observation, in this section we investigated whether the porosity of UiO-66 can be further enhanced by tuning the missing-linker defects.…”
Section: Journal Of the American Chemical Societymentioning
confidence: 99%